2021
DOI: 10.1093/pubmed/fdaa268
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitudes and anxiety toward COVID-19 among domestic and overseas Chinese college students

Abstract: Background To investigate the knowledge, attitudes and anxiety toward COVID-19 among Chinese college students studying in China and abroad. Method A structured questionnaire, comprised of demographic characteristics, knowledge and attitudes toward COVID-19 and the State–Trait Anxiety Inventory (STAI), was used to collect data for 566 domestic students and 126 students studying abroad. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…Students of non-health related curriculums also had elevated STAI results, whereas Turkish female students had mean scores of 45.28 and males of 41.29 points [33]; Italian students had a mean score of 49.8 points [34]. Lower scores were revealed by Chinese students with a mean value of 39.5 points [29]. This proves the replicability of results and overall tendency of increased levels of anxiety among different populations studied by different researchers.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Students of non-health related curriculums also had elevated STAI results, whereas Turkish female students had mean scores of 45.28 and males of 41.29 points [33]; Italian students had a mean score of 49.8 points [34]. Lower scores were revealed by Chinese students with a mean value of 39.5 points [29]. This proves the replicability of results and overall tendency of increased levels of anxiety among different populations studied by different researchers.…”
Section: Discussionsupporting
confidence: 59%
“…Those supplementary questions served as predictors and explanative factors for anxiety levels as main independent variable used in this study. Such questions were commonly practiced in the other anxiety-related studies of students during pandemic [28,29].…”
Section: Measurement Toolsmentioning
confidence: 99%
“…Similarly nursing students from Spain showed anxiety levels which ranged from 50 to 58 points [33], which was concurrent with presented results. Similar results were also obtained from the students in China [34]. Most of the published reviews are limited to prevalence results of anxiety [35][36][37] and its own regression models, without presenting raw STAI results.…”
Section: Discussionsupporting
confidence: 71%
“…However, it is important to note that seroprevalence studies showed a low prevalence of 2.3% early in the pandemic, and this rate rose to 12.2% in another study [24,25]. It is interesting to note that the majority of HCWs were aware of the newly described Delta variant but had much less knowledge about the Delta-Plus variant, which could be explained by the media focusing on the Delta variant, previous study has shown Saudi students having satisfactory knowledge about the COVID-19 but poor knowledge about its mode of transmission and background of the disease highlighting the emphasis of further education and training especially for HCWs in our case about the dynamics of the disease rather than the media quality of knowledge [26][27][28][29]. The low percentage of professionals with a good knowledge of the variant may be related to the source of their information mainly being social networks; this also may be related to the professionals who were included, as 50.9% worked in general wards and OPD and 41.7% were nurses.…”
Section: Discussionmentioning
confidence: 67%